Neurobiology of Language 2016
DOI: 10.1016/b978-0-12-407794-2.00088-2
|View full text |Cite
|
Sign up to set email alerts
|

The Neurocognition of Prosody

Abstract: Prosody is one of the most undervalued components of language, despite fulfilling manifold purposes: it can, for instance, help assign the correct meaning to compounds such as 'white house' (linguistic function), or help a listener understand how a speaker feels (emotional function). However, brain based models that take into account the role prosody plays in dynamic speech comprehension are still rare. This is probably due to the fact that it has proven difficult to fully denote the neurocognitive architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…Banse & Scherer, 1996). Still, while there is an extensive literature devoted to how emotions are conveyed or understood through prosody (see e.g., Paulmann, 2015, for cognitive/social neuroscience review), far less is known about how social viewpoints, beliefs, or attitudes are conveyed or understood (Mitchell & Ross, 2013). This is surprising given how frequently, and in how wide a range of social and communicative contexts such prosody is used.…”
Section: Social Prosodymentioning
confidence: 99%
“…Banse & Scherer, 1996). Still, while there is an extensive literature devoted to how emotions are conveyed or understood through prosody (see e.g., Paulmann, 2015, for cognitive/social neuroscience review), far less is known about how social viewpoints, beliefs, or attitudes are conveyed or understood (Mitchell & Ross, 2013). This is surprising given how frequently, and in how wide a range of social and communicative contexts such prosody is used.…”
Section: Social Prosodymentioning
confidence: 99%
“…As described above, investigators have typically focused on identifying the nature and outcomes of the words speakers select to use when communicating motivation, but new evidence points to the importance of the tone of voice used through which a motivating directive is conveyed. Informed by work on affective prosody (see e.g., Paulmann, 2016, or Mitchell & Ross, 2013, recent work on motivational prosody (Weinstein et al, 2018) has shown that the two motivational qualities of autonomy support and control differ systematically in terms of their acoustic characteristics. Specifically, autonomy-supportive phrasing uses a lower volume and less vocal energy in high frequency bands when compared to intoning controlling phrasing (Weinstein et al, 2018).…”
Section: The Sound Of Motivationmentioning
confidence: 99%
“…Previous neuroimaging studies demonstrated that perception of linguistic intonation involves fronto‐temporal and parietal brain regions in both hemispheres. These regions have been associated with different steps in intonation processing, from basic auditory analysis of pitch via abstraction of pitch contours to subvocal rehearsal and categorical labelling of intonation, for example, as statement or question (for reviews, see Baum & Pell, ; Belyk & Brown, ; Paulmann, ; Witteman, van Ijzendoorn, van de Velde, van Heuven, & Schiller, ). One point of constant debate is the lateralisation of linguistic intonation perception.…”
Section: Introductionmentioning
confidence: 99%